2023
DOI: 10.3390/ijerph20042827
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Insecure Attachment to Parents on Adolescents’ Suicidality

Abstract: Insecure attachment has been identified as a risk factor for adolescent psychopathology and, consequently, for suicidal behavior. We aimed to highlight the relationship between the attachment styles of adolescents and their suicidal behavior and to investigate the role of each parent in the suicidality pathway of adolescents. The sample consisted of 217 adolescent inpatients who were at the highest risk for suicidal behavior and who were hospitalized in the Unit for Intensive Child and Adolescent Psychiatry. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Regarding the hypotheses related to the negative impact of ACEs and the moderating role of attachment insecurity, we only accepted hypothesis (H3), which established that the negative impact of ACEs on psychopathology expressed in externalizing symptoms was more significant the more attachment insecurity the adolescents presented, i.e., when they reported more significant abandonment anxiety in their interpersonal relationships. These results contribute to the development of the attachment theory (Bowlby, 2003 ), particularly to its presence in the adolescent stage, corroborating that insecure attachment is a risk factor for certain psychopathologies in adolescence (Kerns & Brumariu, 2014 ; Leben Novak et al, 2023 ). Furthermore, the effect of ACEs did not exert any influence on externalizing symptoms among individuals with low levels of abandonment anxiety.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regarding the hypotheses related to the negative impact of ACEs and the moderating role of attachment insecurity, we only accepted hypothesis (H3), which established that the negative impact of ACEs on psychopathology expressed in externalizing symptoms was more significant the more attachment insecurity the adolescents presented, i.e., when they reported more significant abandonment anxiety in their interpersonal relationships. These results contribute to the development of the attachment theory (Bowlby, 2003 ), particularly to its presence in the adolescent stage, corroborating that insecure attachment is a risk factor for certain psychopathologies in adolescence (Kerns & Brumariu, 2014 ; Leben Novak et al, 2023 ). Furthermore, the effect of ACEs did not exert any influence on externalizing symptoms among individuals with low levels of abandonment anxiety.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, some authors have suggested that a secure attachment in childhood (Ainsworth et al, 1978 ) could constitute a protective factor against developing mental health problems or psychopathology in childhood and adulthood (Sund & Wichstrøm, 2002 ). Conversely, an insecure attachment could be a risk factor (although not the only cause) for developing mental health problems or psychopathology in adolescence or adulthood (Kerns & Brumariu, 2014 ; Leben Novak et al, 2023 ). In the same vein, it has been shown that secure attachment could have some influence in the prevention of multiple problematic issues such as violent behavior (Franke, 2000 ), post-traumatic stress (Ensink et al, 2021 ), behavioral problems in children (Barone et al, 2016 ; Edwards et al, 2006 ), dementia (Walsh et al, 2019 ), and even cellular aging (Dagan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result can be interpreted as the better the resolution and response effect of parental conflict, the better the parent-child attachment becomes, the lower the risk of suicide keeps. The probable reason for this result may be due to the fact that a good resolution and a good response effect in a conflict lead to a high degree of parent-child attachment, a high degree of parent-child attachment can significantly reduce the risk of suicide in adolescents ( 59 ). Our study findings align with research conducted on Western families, particularly from the United States ( 24 26 ) and Europe ( 18 , 28 ), indicating the significance of a parent-child relationship built on responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Teenagers with high parent-child attachment scores have low risk of suicide, which is consistent with the conclusions of the relevant studies ( 69 ). The reason is that high-quality parent-child attachment will lead to high social adaptability and cultivate positive psychological qualities, in turn, it reduces various negative emotions and bad behaviors including suicide ( 59 ). LBC is also a high risk of suicide, the reason for this may be that LBC lacks parental love from an early age, which can lead to multiple psychological problems, which leads to a higher risk of suicide ( 70 73 ).…”
Section: Discussionmentioning
confidence: 99%